Correction Of Tongue-Tie With A Diode Laser: A Case Report (Journal of Pharmaceutical Negative Results, 2023)
Tongue is an important structure of oral cavity that is responsible for speech, swallowing, taste and positioning of teeth. A frenum is fold of mucous membrane, with enclosed muscle fibers that attaches lips and cheeks to alveolar and /or alveolar mucosa and underlying periosteum. Ankyloglossia or tongue-tie is a clinical condition characterized by decreased mobility of tongue tip due to usually short, thick lingual frenum resulting in limitation of tongue movements. Lingual frenectomy is the procedure that involves removal of tissue band, the lingual frenum, that connects tongue to the floor of the mouth. Laser frenectomy results in lower risk of relapse, such as adhesion and hence the prognosis is superior to those treated by traditional methods. In this article we report a case of a male patient, 34 year with tongue-tie, complaining of difficulty in speech which was treated with laser with an uneventful healing and good patient satisfaction.